Improving the nutritional status of preschool children in El-Menoufia Governorate, Egypt - El.Eskafy, Azza Mohamed Ibrahim; Justus Liebig University Giessen (My University, 2008)
Malnutrition continues to be a major health burden in developing countries. In Egypt, the data of height-for-age Z-score (HAZ) indicated that there was considerable chronic malnutrition among children. Iron deficiency is considered the most prevalent among preschool children, and iron deficiency anemia is considered a moderate public health problem. The main object of the current study was improving the nutritional status of preschool children from low and middle income groups in Egypt by an intervention with locally made snack. The study was designed as a single-blind, placebo-controlled intervention for 8 weeks. 45 children aged 24-47 months were divided into two groups. The first group was the intervention group which received the snack (n = 22), and the second group was the placebo group which received an isocaloric beverage (n = 23). The snack and the beverage were similar only in energy content. Information on the family sociodemographic characteristics and children s dietary habits were obtained during an interview with the mothers. Every child was asked about his/her acceptability of the snacks. 24-hour recall method was used to assess the usual intake of energy and nutrients for two consecutive days. Both at baseline and after the intervention, weight and height were assessed and blood samples were collected from all children. A complete blood cell count was performed and serum ferritin level was determined. The snack was acceptable among the children for their sweet and nice taste. Using the snack had a positive effect on the nutritional status of the preschool children. In the intervention group, the prevalence of stunting and underweight was lower after the intervention than at baseline, and there was no change in the prevalence of wasting. In the placebo group, there was no change in the prevalence of stunting and underweight was found only after the intervention. The prevalence of wasting increased during the intervention. The children in the two study groups showed a significant increment in the mean of height which was higher in the intervention group than in the placebo group (1.67 cm vs. 1.34 cm). There was an increase in the mean value of HAZ after the intervention in the two groups, and the difference between the two groups was significantly higher after the intervention (p = 0.014) than at baseline (p = 0.026). The mean value of weight-for-height Z-score (WHZ) and also of weight-for-age Z-score (WAZ) of the children in the two groups were lower after the intervention compared to baseline. This decrease in WHZ and in WAZ was not significant in the intervention group, however; it was significant in the placebo group. There was a significant increase in the mean intakes of energy and nutrients during the intervention among the children in the intervention group, especially the deficient nutrients. However, there was no change in the nutrient intakes in the placebo group. The blood measurements of the children in the intervention group, particularly the anemic children, improved after the intervention compared with the placebo group. The mean value of haemoglobin increased slightly (0.27 g/dl) in the intervention group, however; there was no change in the placebo group. The children in the two study groups showed a significant increase in the red blood cell counts after the intervention which was significantly higher in the intervention group (p = 0.0001) than in the placebo group (p = 0.001). Furthermore, the prevalence of low ferritin level in the intervention group decreased after the intervention compared to at baseline; however, it increased in the placebo group. The prevalence of anemia among the children in the intervention group was 28.6% at baseline, and it decreased to 19% after the intervention. In the placebo group, there was no change in the prevalence of anemia after the intervention from baseline (19%). After the intervention, the haemoglobin value increased among 4 anemic children in the intervention group, and half of them had haemoglobin >11 g/dl. One anemic child in the placebo group had an increase in the haemoglobin value, but it remained lower than 11 g/dl.It can be concluded that a supplement made from locally available food as a snack showed a success in improving the nutritional status of the preschool children from low and middle income groups in Egypt. The snack was effective in managing iron deficiency among the children in study population.

Mangelernährung ist weiterhin eine der Hauptbelastungen in Entwicklungsländern. In Ägypten weisen die height-for-age Z-score Daten (HAZ) auf eine chronische Mangelernährung unter Kindern hin. Eisenmangel ist bei Vorschulkindern am meisten verbreitet, und Eisenmangelanämie gilt als moderates Volksgesundheitsproblem. In der vorliegenden Studie war das Hauptanliegen, den Ernährungszustand von Vorschulkindern aus Haushalten mit niedrigem und mittlerem Einkommen in Ägypten durch die Gabe eines lokal hergestellten Snacks zu verbessern und so Nährstoffdefizite auszugleichen. Der Aufbau der Studie war eine einfach-blinde, Placebo-kontrollierte Intervention über 8 Wochen. Fünfundvierzig Kinder im Alter von 24-47 Monaten waren aufgeteilt in 2 Gruppen. Die erste Gruppe, (n=22), war die Interventionsgruppe, welche den Snack bekam. Die zweite Gruppe, (n=23), war die Placebogruppe, die mit Getränken versorgt wurde. Der Snack und das Getränk waren gleich im Hinblick auf den Energie-Gehalt. Informationen über den soziodemographischen Hintergrund der Familie und die Ernährungsgewohnheiten des Kindes wurden während eines Interviews mit den Müttern aufgenommen. Jedes teilnehmende Kind wurde über ihre/seine Einstellung und Akzeptanz zum entwickelten Snack befragt. Die 24-hour-recall-Methode wurde genutzt, um die gewöhnliche Menge an Energie- und Nährstoffaufnahme an zwei aufeinander folgenden Tagen zu schätzen. Zu Beginn und nach der Intervention wurden Körpergewicht und Körpergröße gemessen und Blutproben von den Kindern der beiden Gruppen genommen. Es wurde ein Blutbild erstellt und die Serum Ferritin-Level bestimmt. Die Interventionsstudie unter Vorschulkindern durch Einführung eines Snacks als Nahrungssupplement hatte positive Effekte auf den Ernährungsstatus der Kinder. In der Interventionsgruppe war die Prävalenz für Stunting und Untergewicht niedriger nach der Intervention. Es gab keine Unterschiede in der Prävalenz von Wasting. In der Placebogruppe gab es keine Veränderung hinsichtlich der Prävalenz des Stunting, die Prävalenz des Wasting stieg während der Intervention an. Nach der Intervention wurde ein Kind mit Untergewicht erfasst. Die Kinder beider Gruppen zeigten signifikanten Erhöhungen der mittleren Körpergröße, welche in der Interventionsgruppe stärker ausgeprägt war als in der Placebogruppe (1,67cm versus 1,34cm). Ein Anstieg der mittleren HAZ konnte nach der Intervention in beiden Gruppen festgestellt werden, wobei die Differenz zwischen den beiden Gruppen signifikant höher war nach Intervention (p=0,014) als bei Studienbeginn (p=0,026). Der Mittelwert für den Weight-for-hight Z-score (=WHZ-Wert) und den Weight-for-age Z-score (=WAZ-Wert) der Kinder in beiden Gruppen sank nach der Intervention. Dieser Abfall war nicht signifikant in der Interventionsgruppe aber signifikant in der Placebogruppe. Im Hinblick auf die Nährstoffaufnahme ergab sich eine signifikante Steigerung während der Interventionsphase in der Interventionsgruppe bezüglich der im Mittel zugeführten Energiemenge und der Nährstoffe, besonders der defizitären Nährstoffe. In der Placebogruppe konnte keine Änderung in der Nährstoffaufnahme festgestellt werden. Die biochemischen Analyseparameter der Kinder aus der Interventionsgruppe, besonders die anämischen Kinder, verbesserten sich nach Intervention im Vergleich zu der Placebogruppe. Die Mittelwerte für Hämoglobin in der Interventionsgruppe erhöhten sich leicht (um 0,27 g/dl), aber in der Placebogruppe fand sich keine Änderung. Die Kinder der beiden Gruppen zeigten eine signifikante Zunahme des Red-Body-Cell-counts nach der Intervention. Diese Zunahme war in der Interventionsgruppe signifikant höher (p=0,0001) als in der Placebogruppe (p=0,001). Des Weiteren nahm die Prävalenz niedriger Ferritin-Spiegel (< 12µg/l) in der Interventionsgruppe ab, während sie in der Placebogruppe zunahm. Die Prävalenz für Anämie unter den Kindern der Interventionsgruppe betrug 28,6% vor Studienbeginn und sank nach Intervention auf 19% ab. In der Placebogruppe ergab sich kein Unterschied in der Prävalenz der Anämie (19%) nach der Intervention mit dem Getränk. Der Hämoglobinwert stieg in der Interventionsgruppe nach Verabreichung des Snacks bei vier anämischen Kindern. Die Hälfte von ihnen hatte Hämoglobinwerte > 11 g/l. Eines der anämischen Kinder in der Placebogruppe wies nach Intervention mit dem Getränk einen Anstieg des Hämoglobinwertes auf, der Hämoglobinwert lag allerdings unter 11 g/l.Zusammenfassend kann gesagt werden, dass ein Nahrungsergänzungsmittel, verabreicht als Snack, hergestellt aus lokal erhältlichen Lebensmitteln, geeignet ist den Ernährungsstatus von Vorschulkindern aus niedrigen und mittleren Einkommensklassen in Ägypten zu verbessern. Die Snacks waren folglich wirksam in der Behandlung von Eisenmangel bei den Kindern aus der Studienpopulation.
Die Verbesserung des Ernährungsstatus von Kindergartenkindern in El-Menoufia, Ägypten
Keywords: Mangelernährung; Vorschulkinder; Anämie; Intervention; malnutrition; preschoolers; anemia; intervention; ddc:610